Readiness of Health Workers in Facing Catastrophic Disease Emergencies in Remote Areas - Sihombing, Benny (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
This study aims to understand the readiness of health workers in dealing with catastrophic disease emergencies in remote areas using a qualitative descriptive approach through case studies. Data were collected using questionnaires, in-depth interviews, participant observation, and document studies. Respondents consisted of 30 health workers, including 15 doctors, 10 nurses, and 5 other medical personnel, with the majority having more than 5 years of work experience and having attended emergency training. The results of the study indicate that health workers have a sufficient level of knowledge in handling emergencies, but practical skills in the use of emergency medical equipment and the implementation of communication protocols still need to be improved. Their attitudes towards emergency situations are generally positive, although some expressed concerns regarding limited facilities and resources. Factors that influence the readiness of health workers include education level, work experience, and support from the government and non-governmental organizations. Recommendations from this study include improving ongoing training, providing more adequate medical equipment, and strengthening coordination between related institutions. In addition, the involvement of local communities in preparedness efforts is also needed to improve the response to emergency situations. In conclusion, the readiness of health workers in dealing with catastrophic disease emergencies is greatly influenced by training, medical facilities, and cross-sector coordination. By improving these aspects, it is hoped that health workers in remote areas can provide a faster and more effective response in dealing with emergency conditions.